Can pricing deter adolescents and young adults from starting to drink: An analysis of the effect of alcohol taxation on drinking initiation among Thai adolescents and young adults. (December 2015) - Sornpaisarn, Bundit; Shield, Kevin D.; Cohen, Joanna E.; Schwartz, Robert; Rehm, Jürgen
Highlights: Maintaining high rates of abstention from alcohol is imperative to prevent the negative consequences of alcohol consumption in low- and middle-income countries (LMICs). This is the first study in an LMIC that examined the effect of alcohol taxation on drinking initiation prevention, and found that tax increases were associated with the prevention of drinking initiation among youth 15–24 years of age in Thailand. Increasing alcohol excise taxation, supplementary to other alcohol control policies, could prevent drinking initiation among young people in countries with a high rate of abstainers. Abstract: The objective of this study is to assess the relationship between alcohol taxation changes and drinking initiation among adolescents and young adults (collectively "youth") in Thailand (a middle-income country). Using a survey panel, this study undertook an age-period-cohort analysis using four large-scale national cross-sectional surveys of alcohol consumption performed in Thailand in 2001, 2004, 2007 and 2011 ( n  = 87, 176 Thai youth, 15–24 years of age) to test the hypothesis that changes in the inflation-adjusted alcohol taxation rates are associated with drinking initiation. Regression analyses were used to examine the association between inflation-adjusted taxation increases and the prevalence of lifetime drinkers. After adjusting for potential confounders, clear cohort and age effects were observed. Furthermore, a 10% increase of the inflation-adjusted taxation rate of the total alcohol market was significantly associated with a 4.3% reduction in the prevalence of lifetime drinking among Thai youth. In conclusion, tax rate changes in Thailand from 2001 to 2011 were associated with drinking initiation among youth. Accordingly, increases in taxation may prevent drinking initiation among youth in countries with a high prevalence of abstainers and may reduce the harms caused by alcohol.